Occipital Neuralgia. A Case Report - Urbano Solis Cartas; Olga Gloria Barbón Pérez; Eduardo Lino Bascó Fuentes (Medisur)
Occipital neuralgia or Arnold's neuralgia is a rare condition that primarily affects women. There are multiple causes that can trigger this disorder, which is clinically characterized by the presence of pain of varying intensity, characteristic radiation of pain and presence of trigger points. Occipital nerve block can be an important element in the diagnosis of the condition. The intensity, frequency and characteristics of pain can considerably limit the perception of quality of life of patients who suffer from it. The case of a 57-year-old patient with a diagnosis of rheumatoid arthritis and symptoms compatible with occipital neuralgia is presented. This case is of interest given the frequent emergency department visits by patients with neck pain and the scarcity of studies on this condition